2016
DOI: 10.1038/srep32308
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Lidocaine in Laryngospasm Prevention in Pediatric Surgery: a Network Meta-analysis

Abstract: Higher incidence and worse outcomes of laryngospasm during general anesthesia in children than adults have been reported for many years, but few prevention measures are put forward. Efficacy of lidocaine in laryngospasm prevention has been argued for many years and we decided to design this network meta-analysis to assess the efficacy of lidocaine. We conducted an electronic search of six sources and finally included 12 Randomized Controlled Trials including 1416 patients. A direct comparison between lidocaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…A bolus of 2 mg/kg of intravenous lidocaine has been shown to reduce the rate of laryngospasm elicited by intentional stimulation of the glottis by distilled water but this effect is short lived 30 . Additionally, a meta‐analysis has demonstrated that topical or intravenous lidocaine is effective at reducing or preventing laryngospasm in children 31 . The major limitations of this meta‐analysis, however, were the relatively low incidence of laryngospasm overall and the fact that anesthesiologists were commonly not blinded to the study group, which alone may have introduced significant reporting bias.…”
Section: Main Articlementioning
confidence: 99%
“…A bolus of 2 mg/kg of intravenous lidocaine has been shown to reduce the rate of laryngospasm elicited by intentional stimulation of the glottis by distilled water but this effect is short lived 30 . Additionally, a meta‐analysis has demonstrated that topical or intravenous lidocaine is effective at reducing or preventing laryngospasm in children 31 . The major limitations of this meta‐analysis, however, were the relatively low incidence of laryngospasm overall and the fact that anesthesiologists were commonly not blinded to the study group, which alone may have introduced significant reporting bias.…”
Section: Main Articlementioning
confidence: 99%
“…75,77 In addition, the use of intravenous or laryngotracheal topical lidocaine has been demonstrated to decrease the risk of laryngospasm in both children and adults. 78,79…”
Section: Discussionmentioning
confidence: 99%
“…11 Topical and IV lidocaine has blunted the incidence of laryngospasm and cough response in people and dogs, respectively. 12,13 Abolition of laryngeal response based on electromyographic studies was recorded 90-120 s after topical application of 2% lidocaine in another study. 4 Intubation was easily performed 1.5 mins after application of 2% lidocaine and loss of response to mechanical stimulation after 1.95 mins.…”
Section: Discussionmentioning
confidence: 99%
“…11 Topical and IV lidocaine has blunted the incidence of laryngospasm and cough response in people and dogs, respectively. 12,13…”
Section: Discussionmentioning
confidence: 99%